Hepatoprotective Role of AV/LCP/18 In CCl4 Induced FLKS Syndrome in Commercial Broilers - Sonkusale, P. M.; lnglepatil , Pratik N.; Jamadade , Siddharth V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A total of 75 day old broiler chicks were divided into three equal groups. Group A served as negative control. Group B (positive control) and C (treatment group) were intoxicated with oral administration of CCl4 @ 1 ml/kg body weight after every 3rd day during 15-28 days of age. Group C was given AV/LCP/18 @ 0.10 ml / chick / day in drinking water during 29th-42nd day of age. At the end of experiment, significantly (P<0.01) higher mean body weight and lower FCR was observed in treatment group C as compared to positive control group B. Similarly, significantly (P<0.05) decreased levels of SGOT, SGPT, cholesterol, triglycerides, creatinine and higher mean values of serum protein profile along with mild degenerative changes in liver and kidney of broilers in group C were observed as compared to group B indicating therapeutic efficacy of AV/LCP/18 in ameliorating the toxic effects or FLKS induced by CCl4 in commercial broilers.